Using, risking, and consent: Why risking harm to bystanders is morally different from risking harm to research subjects. - Walen, Alec (Bioethics, 2020)
Subjects in studies on humans are used as a means of conducting the research and achieving whatever good would justify putting them at risk. Accordingly, consent must normally be obtained before subjects are exposed to any substantial risks to their welfare. Bystanders are also often put at risk, but they are not used as a means. Accordingly—or so I argue—consent is more often unnecessary before bystanders are exposed to similar substantial risks to their welfare.